Review of health hazards and control strategies of sugar-sweetened beverages - Liping SHEN; Zhengyuan WANG; Jing FAN; Caicui DING; Jiajie ZANG (环境与职业医学, 2023)
The global production and consumption of sugar-sweetened beverages (SSBs) has been on the rise in recent decades. The intake of SSBs has been increasing in China, and it is more prevalent among children and adolescents. As research continues to intensify, more and more studies have shown that, in addition to the increased risks of dental caries and obesity reported by the World Health Organization (WHO), SSBs intake can also increase risks of chronic diseases such as diabetes, cardiovascular disease, gout, and cancer, and early death, adding to the burden of disease. Due to the health risks associated with the overconsumption of SSBs, many countries around the world have taken measures to control the intake. The main measures currently in place are taxation of SSBs, restrictions on marketing and sales of SSBs, front-of-package labeling and reducing availability of SSBs in schools. In China, the main measures currently in place are to control the sales of beverages in schools, with Shenzhen taking the lead in implementing health warning labeling to alcoholic beverages and carbonated beverages, extending the measures to reduce SSBs intake beyond school grounds.